Effect on microstructure of Fe80B13Si7 metallic glass irradiated by high intensity pulsed ion beam and He ions - Li Na; Zhang Lisong; Zhang Xiaonan; Cao Xingzhong; Zhang Peng; Guo Yuting; Gong Liyue; Mei Xianxiu; Wang Younian; Pavlov S. K. Sergey Konstantinovich; Remnev (Remnyov) G. E. Gennady Efimovich (2022, 2022)
Title screen